Effect of Long-Term Fertilization on Ammonia-Oxidizing Microorganisms and Nitrification in Brown Soil of Northeast China - Cai, Fangfang; Luo, Peiyu; Yang, Jinfeng; Irfan, Muhammad; Zhang, Shiyu; An, Ning; Dai, Jian; Han, Xiaori (Frontiers in Microbiology, 2021)
The objective of this study was to find out changes in ammonia oxidation microorganisms with respect to fertilizer and investigated by real-time PCR and high throughput sequencing. The treatments included control treatment (CK); chemical fertilizer nitrogen low (N) and high (N2); nitrogen and phosphorus (NP); nitrogen phosphorus and potassium (NPK); organic manure fertilizer (M); MN; MN2; MNPK. The results showed that long-term fertilization influenced soil fertility, and affected the abundance and community of ammonia-oxidizing microorganisms by changing the physical and chemical properties of the soil. The abundance and community structure of Ammonia Oxidizing Archaea (AOA) and Ammonia Oxidizing Bacteria (AOB) was influenced by soil organic carbon, total nitrogen, total soil phosphorus, available phosphorus, available potassium and soil nitrate. Soil environmental factors affect the nitrification potential by affecting the structure of ammonia-oxidizing microorganisms; specific and rare AOA and AOB rather than the whole AOA or AOB community played dominate role in nitrification.